Variety Concept in Designing A Trading Area (Case Study: Dauh Puri Kangin, Denpasar City, Indonesia) - Putu Bulan Ratna Anggraeni; Purwanita Setijanti; Asri Dinapradipta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
Variety is the extent to which design can give a choice of activities, types of users, functions, and meanings that occur in an environment. Feasibility of variety is fundamental in supporting the design quality of the trading area, especially in regions that have priority in developing the trading area, such as in Denpasar City. The economy of Denpasar City depends mostly on the trading sector. However, Dauh Puri Kangin, as the trade center area in the city, still has physical and non-physical problems and has not been well developed. In getting a solution, this place needs research to find design criteria that can increase environmental variety. The study used cognitive mapping methods for data collection and qualitative assessment techniques for analysis methods. The analysis process results in the conditions of the problem and the potential related to variations in the study site. Then, it becomes a consideration in the design criteria of the trading area. From the results of the analysis, the problem that occurs in the corridor facilities is have not been able to accommodate the activities of all types of users, both regular users and users with special needs. Based on the results of the analysis, some considerations for the redesign of the area proposed several design proposals related to architectural design, landscape planning, and pedestrian facilities.